Pengaruh Media Pembelajaran Power Point Terhadap Motivasi Kepada Siswa Sekolah Menengah Kejuruan (SMK) - Fadlin Fajri Tanjung; Irma Nur Azizzah; Sumiati Sumiati; Lavega Lavega (Yayasan Rahmat Islamiyah, 2020)
Abstract: This study aims to determine the function and motivation to learn from Microsoft Office media, namely Microsoft Power Point for students in vocational high schools (SMK). The subject of this study was aimed at several vocational students in the city of Medan. The background of this research was carried out because it saw a lack of application and motivation in using power point media. This study uses qualitative methods which use library references such as books, journals, print media, and learning blogs. The results of this study are expected that vocational students are able to use power point media as a medium in carrying out teaching and learning activities and increase their motivation to be creative in learning itself. Keywords: Power Point Learning Media, Motivation, students